Performance and biocompatibility of OSTEMER 322 in cell-based microfluidic applications - Aubrecht, Petr; Smejkal, Jiří; Panuška, Petr; Španbauerová, Klára; Neubertová, Viktorie; Kaule, Pavel; Matoušek, Jindřich; Vinopal, Stanislav; Liegertová, Michaela; Štofik, Marcel; Malý, Jan (RSC advances, 2024)
The Off-Stoichiometry Thiol-ene and Epoxy (OSTE+) polymer technology has been increasingly utilised in the field of microfluidics and lab-on-a-chip applications. However, the impact of OSTEMER polymers, specifically the OSTEMER 322 formulation, on cell viability has remained limited. In this work, we thoroughly explored the biocompatibility of this commercial OSTEMER formulation, along with various surface modifications, through a broad range of cell types, from fibroblasts to epithelial cells. We employed cell viability and confluence assays to evaluate the performance of the material and its modified variants in cell culturing. The properties of the pristine and modified OSTEMER were also investigated using surface characterization methods including contact angle, zeta potential, and X-ray photoelectron spectroscopy. Mass spectrometry analysis confirmed the absence of leaching constituents from OSTEMER, indicating its safety for cell-based applications. Our findings demonstrated that cell viability on OSTEMER surfaces is sufficient for typical cell culture experiments, suggesting OSTEMER 322 is a suitable material for a variety of cell-based assays in microfluidic devices.